2020
DOI: 10.22214/ijraset.2020.4078
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanical Properties of Polyster & Fly Ash Fiber Reinforced Polymer Composites

Abstract: In this research, Fibre Reinforced Polymer artificial composites are fabricated as a high-strength and lightweight. The artificial fibre of e-glass fibre and fly ash powder are used as a particulate reinforcement for our application. The mechanical strength of these fibre composites is improved by analysis and testing with different compositions of resin, catalyst and accelerator presented in this fibre. The composite samples were fabricated at varying particulate weight content (%) and at room temperature. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…The same result was discussed by the author that the increase in Fly ash to polyethylene leads to increase in Flexural strength and modulus [4]. Gummadi et al also reported that flexural modulus increases for smaller filler loadings [6]. Figure 3 shows that by increasing the filler mass percentage from 0% to 30% hardness of composite increases, as filler enhanced the surface property of composite and resist deformation by penetration, that means reinforcement of lime ash particles reduces the elasticity of polymer chains resulting to a more rigid polymer [7][8][9][10].…”
Section: Flexural Propertiessupporting
confidence: 68%
“…The same result was discussed by the author that the increase in Fly ash to polyethylene leads to increase in Flexural strength and modulus [4]. Gummadi et al also reported that flexural modulus increases for smaller filler loadings [6]. Figure 3 shows that by increasing the filler mass percentage from 0% to 30% hardness of composite increases, as filler enhanced the surface property of composite and resist deformation by penetration, that means reinforcement of lime ash particles reduces the elasticity of polymer chains resulting to a more rigid polymer [7][8][9][10].…”
Section: Flexural Propertiessupporting
confidence: 68%
“…Instead, the modulus of elasticity of the composites increased by 10-14% (Figure 9b). Gummadi et al [19] studied the flexural behavior of PP composites with ash and showed that by adding 10% ash with small particles (53-75 µm) and showed the flexural modulus and strength can be increased by 5% and 27%, respectively, but with a decrease in elongation at break by 18%. With larger particles (76-105 µm), the elongation at break decreased by half, and the flexural modulus decreased by 5%.…”
Section: Mechanical and Dynamic Mechanical Analysismentioning
confidence: 99%
“…Nath et al [18] demonstrated that, compared to PP, injection-molded PP composites with 20-60% fly ash with a particle size of 5-60 µm exhibited a 10-60% higher modulus of elasticity, but a linear decrease in tensile strength at 25 • C and a substantial increase in tensile and impact strength at 50-70 • C. Composites based on PP with 10% ash with 53-75 µm particle sizes showed an improvement in flexural strength by approx. 30% [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been performed to introduce this waste material as a low-cost filler by itself or in various combinations with organic or inorganic materials [4][5][6][7]. In addition to these studies, fly ash was discovered to act as a reinforcing agent in a study by Satheesh et al [8], where good interaction between the ash and the matrix was achieved, while a study by Nath et al [9] and Gummadi et al [10] pointed out that the properties of PP composites with fly ash content are dependent on the particle size of said ash. In a study performed by Kutchko and Kim [11], it is pointed out that smaller-particle-size fly ash leads to better mechanical properties as long as the particles are well dispersed in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%